2020
DOI: 10.7554/elife.51507
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trajectories, correlations and mortality associations of nine biological ages across 20-years follow-up

Abstract: Biological age measurements (BAs) assess aging-related physiological change and predict health risks among individuals of the same chronological age (CA). Multiple BAs have been proposed and are well studied individually but not jointly. We included 845 individuals and 3973 repeated measurements from a Swedish population-based cohort and examined longitudinal trajectories, correlations, and mortality associations of nine BAs across 20 years follow-up. We found the longitudinal growth of functional BAs accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
206
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(219 citation statements)
references
References 35 publications
13
206
0
Order By: Relevance
“…Biological aging seems to be differently manifested at certain cellular levels, as suggested by the range of correlations among the biological clocks considered in this study. Consistent with prior studies we showed weak correlations between different biological clocks 26 and we confirm the absent relationship between telomere length and the epigenetic clock 21,27,28 , but also show lack of associations with the transcriptomic, proteomic or metabolomic clocks. However, we do confirm an earlier finding showing a significant but modest correlation between epigenetic and transcriptomic age 29 .…”
Section: Discussionsupporting
confidence: 92%
“…Biological aging seems to be differently manifested at certain cellular levels, as suggested by the range of correlations among the biological clocks considered in this study. Consistent with prior studies we showed weak correlations between different biological clocks 26 and we confirm the absent relationship between telomere length and the epigenetic clock 21,27,28 , but also show lack of associations with the transcriptomic, proteomic or metabolomic clocks. However, we do confirm an earlier finding showing a significant but modest correlation between epigenetic and transcriptomic age 29 .…”
Section: Discussionsupporting
confidence: 92%
“…In general, weight loss in late life was associated with an increased mortality [8]. Malnutrition in older adults with cancer may diminish tolerance to therapy and result in a worse response to treatment [9].…”
Section: Management Of Older Adult Cancer Patientsmentioning
confidence: 99%
“…Two such predictors, termed PhenoAge (a DNAm predictor trained on a measure that itself was trained on mortality, using 42 clinical measures and age as input features) and GrimAge (trained on mortality, including a DNAm measure of smoking as a constituent part), outperform both Hannum and Horvath clocks in predicting mortality, and are associated with various measures of morbidity and lifestyle factors [15,16]. DNAm GrimAge outperforms PhenoAge and the first generation of epigenetic clocks when it comes to predicting time to death [8,17,18].…”
Section: Introductionmentioning
confidence: 99%